Solar Flux Influence on the In‐Situ Plasma Density at Topside Ionosphere Measured by Swarm Satellites. Issue 5 (29th April 2022) - Xiong, Chao; Jiang, Haicheng; Yan, Rui; Lühr, Hermann; Stolle, Claudia; Yin, Fan; Smirnov, Artem; Piersanti, Mirko; Liu, Yiwen; Wan, Xin; Diego, Piero; Zhima, Zeren; et al.
Abstract: In this study, we perform the first comprehensive comparison of ion density (Ni) in the topside ionosphere measured by the Langmuir probe (LP) and faceplate (FP) of the thermal ion imager on board Swarm satellites. Our results show a systematic difference between the LP and FP derived Ni values, and the systematic difference shows prominent dependences on solar flux, local time, and season. Although both Ni datasets show generally good linear regression with electron density (Ne) measurements from the incoherent scatter radar (ISR) located at Jicamarca, the Ni derived from LP shows an additional dependence on the solar flux, while such a dependence cannot be seen in the FP‐derived Ni. We suggest that the solar flux dependence of LP‐derived Ni is related to the ion compositions change at Swarm altitude, which has not been properly accounted for in the LP processing algorithm. More light ions (e.g., H + ), diffusing down from the plasmasphere to the Swarm altitude, seem to cause the overestimation of Ni from LP during low solar activity. A linear relation between the Swarm LP‐derived Ni and ISR Ne is derived, and such a function is recommended to be implemented into further updates of the Swarm LP plasma density data. Key Points: First comprehensive comparison of Ni measured by the Langmuir probe (LP) and faceplate (FP) on board Swarm satellites is performed There exists a systematic difference between the LP and FP derived Ni values, and it varies with solar flux, local time, and season LP‐derived Ni shows a clear dependence on solar flux, caused by ion compositions change at Swarm altitude during low solar flux years